EVALUASI SIFAT REOLOGI DASAR PADA CAMPURAN ASPAL MODIFIKASI KARET REMAH SIR 20 - fitra ramdhani (LPPM Universitas Abdurrab, 2019)
Utilization of natural rubber in oil asphalt mixes scientifically possible to improve asphalt technology by evaluating the rheological properties of the asphalt. Crumb rubber is natural rubber obtained from processing rubber materials which comes from the sap of the Hevea brasiliensis tree trunk mechanically with or without chemicals and the quality is determined by technical specifications SIR (Standar Indonesia Rubber). The purpose of this study was to determine the basic rheological properties of the modified SIR 20 crumb rubber asphalt mixture. This research method was carried out in two stages, the first is to make a mixture of 60/70 pen asphalt and crumb rubber SIR 20 in the variation of crumb rubber content of 0%, 4%, 6%, 7%, 8%, 9%, 10% , and 20% while the second is to perform asphalt basic testing, which penetration testing, softening point, ductility, elastic recovery and asphalt viscosity. From the test results obtained penetration values ​​increased up to 180,4 dmm, decreased softening point up to 36,450C, increased ductility values ​​consistently up to 195 cm, consistently increase ductility values up to 195 cm, improvement of elastic recovery each additional level of Crumb Rubber SIR 20 to 21.34%, and viscosity (Brookfield) at mixing temperature test were obtained at 1460C and the lower the solidification temperature reached 1370C.